PENGEMBANGAN INDUSTRI OLAHAN MAKANAN KOTA SUNGAI PENUH PROVINSI JAMBI - Chatra, Afdhal (Bussman Journal : Indonesian Journal of Business and Management, 2021)
This study aims to determine the strategy for developing the food processing industry in Sungai Penuh City in the future. The analysis used in this research is SWOT analysis. Based on the results of the SWOT analysis, the strengths and weaknesses of the food processing industry in Sungai Penuh City are balanced in number, as well as in terms of opportunities and threats are also balanced. This can be interpreted that the position of the food processing industry in Sungai Penuh City is in an average condition. The possibility to develop is still open, meaning that it can choose which alternative will be applied